2019
DOI: 10.1029/2018pa003380
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mechanisms and Uncertainty in Modeled Climatic Change at the Eocene‐Oligocene Transition

Abstract: The Earth system changed dramatically across the Eocene‐Oligocene Transition (EOT) on a variety of spatial and temporal scales. Understanding the many complex and interacting factors affecting the Earth's atmosphere and oceans at the EOT requires the combination of both data and modeling approaches and an understanding of the uncertainty in both of these elements. Here uncertainty in the Earth system response to various imposed forcings typical of changes at the EOT is assessed. By using an ensemble of simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 64 publications
(96 reference statements)
6
39
0
Order By: Relevance
“…A second option that could partly explain the model-data discrepancy is that local-to regional-scale warming signals in response to Antarctic glaciation due to enhanced circulation, deepwater formation and sea ice feedbacks (as identified in models by Goldner et al, 2014;Knorr and Lohmann, 2014;Kennedy et al, 2015;; and some of the FOAM simulations used here from Ladant et al, 2014; figure not shown) could be compensating for some of the cooling. When this warming is combined with a pCO 2 decline, the models do suggest that some very localized areas (i.e.…”
Section: Discrepancies and Uncertainty In The Latitudinal Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…A second option that could partly explain the model-data discrepancy is that local-to regional-scale warming signals in response to Antarctic glaciation due to enhanced circulation, deepwater formation and sea ice feedbacks (as identified in models by Goldner et al, 2014;Knorr and Lohmann, 2014;Kennedy et al, 2015;; and some of the FOAM simulations used here from Ladant et al, 2014; figure not shown) could be compensating for some of the cooling. When this warming is combined with a pCO 2 decline, the models do suggest that some very localized areas (i.e.…”
Section: Discrepancies and Uncertainty In The Latitudinal Temperaturementioning
confidence: 99%
“…Global cooling and the significant expansion of glacial ice over Antarctica at the Eocene-Oligocene transition (EOT) ∼ 33.7 million years ago (Myr; Zachos et al, 2001;Coxall et al, 2005) would have potentially resulted in large but uncertain changes in the Southern Ocean and the climate of the high-latitude Southern Hemisphere (Bohaty et al, 2012;Passchier et al, 2013). Numerous palaeoclimate modelling studies have shown that changes in Antarctic Ice Sheet extent, atmospheric pCO 2 levels and palaeogeographic reconstruction around this period of the Earth's history can all impact the modelled global and/or regional climate (Goldner et al, 2014;Knorr and Lohmann, 2014;Kennedy et al, 2015). Interestingly, all of these studies show some areas of warming in the Southern Ocean in response to the imposition of an Antarctic Ice Sheet in their models, but the different models find the warming to occur in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, DP opening in the low-resolution FOAM general circulation model produces a smaller impact in terms of temperature and ocean circulation in an Eocene configuration with high CO 2 levels compared to a modern one (Zhang et al, 2010(Zhang et al, ). et al, 2015Kennedy-Asser et al, 2019;Vahlenkamp et al, 2018). These studies describe an ACC with a moderate intensity during the Eocene/Oligocene (around 4 to 46.2 Sv; Kennedy et al, 2015), which strengthens as a result of pCO 2 decrease, Antarctic Ice Sheet formation, and opening of the Southern Ocean (up to 89 Sv; Hill et al, 2013;Kennedy et al, 2015;Ladant et al, 2014a;Lefebvre et al, 2012;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…These studies describe an ACC with a moderate intensity during the Eocene/Oligocene (around 4 to 46.2 Sv; Kennedy et al, 2015), which strengthens as a result of pCO 2 decrease, Antarctic Ice Sheet formation, and opening of the Southern Ocean (up to 89 Sv; Hill et al, 2013;Kennedy et al, 2015;Ladant et al, 2014a;Lefebvre et al, 2012;Zhang et al, 2010). Among these studies, the impact of DP opening on temperatures is variable with either a regional cooling of the Atlantic sector of the Southern Ocean (up to 6°C; Kennedy et al, 2015;Kennedy-Asser et al, 2019) or quasi-insignificant temperature changes (<1°C) (e.g., Goldner et al, 2014;Inglis et al, 2015;Zhang et al, 2010). Goldner et al (2014) have illustrated the particularly weak contribution of the opening of Southern gateways to EOT ocean temperature changes, in comparison to pCO 2 decrease or Antarctic Ice Sheet build-up.…”
Section: Introductionmentioning
confidence: 99%
“…Value from Francis et al, 2009 (p.333 The model simulations used here have been previously described in Kennedy-Asser et al (2019) and Ladant et al (2014). 60…”
Section: Plateaumentioning
confidence: 99%